Vídeo para cuidadores de idosos: aspectos da alimentação e comunicação - Cunha, Divany Guedes Pereira da (2018)
Introduction: Brazil has been undergoing changes in its demographic profile due to the reduction in the rate of mortality and increased life expectancy. The World report on Health and Aging stated that the number of people aged over 60 in the country should grow much faster than the international average. As a result, it has become essential to invest in studies about the aging process and all the content that permeates even the orientation directed to caregivers for the elderly. The rationale of this study consists in the fact that elderly people who have trained caregivers with respect to the roles of power and communication have better prognosis, being such findings evidenced in ambulatory care speech. Objectives: 1. Identify and analyze studies on the dysphagia in institutionalized elderly; 2. Identify and analyze studies on language and cognition in the elderly; 3. Analyze the knowledge of formal caregivers with respect to aspects of the power and communication of the elderly person and draw up a video with guidelines for the formal caregiver. Method: This is a methodological study of quantitative approach. The research was performed in four long-term institutions, in the municipality of João Pessoa. The sample corresponded to the population and was composed by all caregivers of elderly institutions, totaling 34 volunteers. The project was submitted to the Research Ethics Committee at the Health Sciences Center of the Federal University of Paraiba and approved by N 2,190.153, 27th July, 2017, CAAE; 67103917.6.0000.5188. Results: This study originated three articles: two for qualification and one for defense. The first review of the literature on the analysis of the studies related to the dysphagia in long term care institutions, which showed the existence of risk to the dysphagia in this context as well as lack of knowledge of professionals with regard to strategies that minimize the risk of laryngeal aspiration. The second article was a review of the literature on language and cognition in the elderly and the results showed that the aging process entails linguistic and cognitive changes, emphasizing the importance of the cognitive training for memory, language, communication and socialization of the elderly person. . The third article (original) analyzed the knowledge of caregivers of elderly on aspects of communication and power, showing that they are aware of the difficulties of speech, hearing, and cognition of the elderly and of strategies that facilitate these functions. Also has no knowledge of feeding difficulties although performed facilitative practices. Conclusions: The reviews of the literature showed that the process of aging is related to dysphagia, declines in language and cognition. The article of defense confirmed the importance of video to guide the caregivers of elderly with respect to power and communication, enabling an improvement in the quality of life in long term care institutions.